2015
DOI: 10.1007/s00122-015-2522-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Soybean mosaic virus resistance derived from inverted repeat-SMV-HC-Pro genes in multiple soybean cultivars

Abstract: Soybean mosaic virus resistance was significantly improved in multiple soybean cultivars through genetic transformation induced by inverted repeat-SMV- HC - Pro genes based on RNAi and post-transcriptional gene silencing. Here, we demonstrate Soybean mosaic virus (SMV) resistance in transgenic soybean plants. Transformation of five soybean genotypes with a construct containing inverted repeat-SMV-HC-Pro genes-induced high-level SMV resistance. Through leaf-painting assays, polymerase chain reaction (PCR) verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…In this study, we used a modified half-seed method to transform a Korean cultivar, with a transformation efficiency of about 3 %. This is similar to the efficiency rate reported by Gao et al (2015), but lower than that of our previous experiment (Kim et al 2013). A transformation efficiency of about 3 % is not highly efficient, but is enough to produce more than 20 transgenic plants from 500 explant seeds.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, we used a modified half-seed method to transform a Korean cultivar, with a transformation efficiency of about 3 %. This is similar to the efficiency rate reported by Gao et al (2015), but lower than that of our previous experiment (Kim et al 2013). A transformation efficiency of about 3 % is not highly efficient, but is enough to produce more than 20 transgenic plants from 500 explant seeds.…”
Section: Discussionsupporting
confidence: 85%
“…Due to its limitation of SMV-CP RNAi for SMV resistance in soybean, HC-Pro was used to produce strong and complete resistance. Recently, Gao et al (2015) reported results similar to ours, obtained by producing SMV-resistant soybean plants of Chinese cultivars using an HC-Pro gene fragment from SMV SC3 strain via RNAi. One small difference is the presence of viral transcript after the SMV inoculation of transgenic plants; in our study, no accumulation of viral transcript was detected in resistant T 2 plants and T 3 seeds, via either northern blot analysis or reverse transcriptase PCR and quantitative real-time PCR analysis; however, a gradual decrease or low level of viral transcript accumulation was detected in T 1 plants via qRT-PCR during their study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The multiple soybean cultivars transformed with an RNA interference (RNAi) construct targeted for SMV HC-Pro displayed a significantly enhanced resistance against SMV (Gao et al, 2015). Soybean plants transformed with a single RNAi construct expressing separate short hairpins or inverted repeat (IR) (150 bp) derived from three different viruses (SMV, Alfalfa mosaic virus, and Bean pod mottle virus) confer robust systemic resistance to these viruses (Zhang et al, 2011).…”
Section: Small Rna Pathways In Smv Resistancementioning
confidence: 99%
“…Stable transgenic plants for a variety of crops were generated expressing small RNAs in different ways and their reactions to targeted viruses were tested in both laboratory and field condition ( Supplementary Table S1 ). In some studies, the durability of resistance was tested for many generations (Wang et al, 2001, 2016; Liu et al, 2007; Cruz et al, 2014; Faria et al, 2014). According to the International Service for the Acquisition of Agri-Biotech Applications (ISAAA) website, dozens of transgenic crops resistance to virus generated with SRGE were approved for commercial release ( Supplementary Table S2 ).…”
Section: Application Status Of Srge In Crop Protectionmentioning
confidence: 99%